Determinant Factors of Energy Consumption Savings in Urban Households - Ambarwati, Sri; Sudarmaji, Eka (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Based on urban homes' typical features and socioeconomic characteristics, this experimental research examined consumer behavior patterns regarding energy efficiency and the factors influencing energy saving. This research investigated the idea of